If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 = 6x + 1 Reorder the terms: 4 + 9x = 6x + 1 Reorder the terms: 4 + 9x = 1 + 6x Solving 4 + 9x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + 9x + -6x = 1 + 6x + -6x Combine like terms: 9x + -6x = 3x 4 + 3x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + 3x = 1 + 0 4 + 3x = 1 Add '-4' to each side of the equation. 4 + -4 + 3x = 1 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 1 + -4 3x = 1 + -4 Combine like terms: 1 + -4 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| n+(-8)=6 | | (2x+3)+(x-7)=40 | | 7x+5-x=17 | | -1(8n-2)=3+10-30n | | -3x+8+2x=15 | | 15=-3(5x+5) | | 12x-48=30 | | -4(-6x+8)=16 | | y=(-9)-2x | | -5(4t-3)+9t=2t-8 | | 12x-(9x-5)=17 | | 2(x-2)=5(x+3) | | 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= |